PEMANFAATAN IKAN PORA-PORA SEBAGAI BAHAN BAKU TAMBAHAN PEMBUATAN KERUPUK DAN DAYA TERIMANYA - yati oktaviani br keliat; zulhaida lubis; albiner siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Crackers that is made with the addition of pora-pora fish is expected to increase the diversity of fish crackers that has been on the market and also increase the nutritional value of the cracker itself. The purpose of this study was to determine the effect of pora-pora fish to the nutrients composition and acceptability of crackers. This research use experimental design consisting of a treatment i.e the addition of pora-pora fish in making crackers with three concentrations (5%, 10%, and 15%). Protein content of pora-pora fish crackers P1, P2, and P3 is 2,00%, 4,11%, and 6,40%. Calcium content of pora-pora fish crackers P1, P2, and P3 is 28,6 mg, 51,3 mg, 77,1 mg. Based on organoleptic test of color and texture the most preferred is crackers with the addition of pora-pora fish 5%, while the flavor and taste the most preferred is cracker with the addition of pora-pora fish 15%. Based on the analysis of variance, the addition of pora-pora fish with deffrent concentration in making crackers gave a significantly different effect on the color and texture, but the addition of fish pora-pora different concentration, does not give a different effect on the flavor and taste of the crackers. It is suggestioned for consumer to make pora-pora fish crackers as an alternative food precent variations in household and industry levels. Also be made to introduce pora-pora fish crackers to cooperate with the school canteen and other foods made with the addition of the diversification of pora-pora fish. Keyword : Crackers, Pora-Pora Fish, Acceptability Test